2018
DOI: 10.1002/bjs.10990
|View full text |Cite
|
Sign up to set email alerts
|

INTEND II randomized clinical trial of intraoperative duct endoscopy in pathological nipple discharge

Abstract: Background The majority of lesions resulting in pathological nipple discharge are benign. Conventional surgery is undirected and targeting the causative lesion by duct endoscopy may enable more accurate surgery with fewer complications. Methods Patients requiring microdochectomy and/or major duct excision were randomized to duct endoscopy or no duct endoscopy before surgery. Primary endpoints were successful visualization of the pathological lesion in patients randomized to duct endoscopy, and a comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Sensitivity, specificity, and negative predictive values were similar to previously conducted research in patients with an increased risk for the development of breast cancer. 33 All other results are in line with previous studies conducted. [20][21][22]28,29,31 In recent years, MRI is sometimes used to find the cause of PND.…”
Section: Mando Dyko Filipe Et Alsupporting
confidence: 92%
“…Sensitivity, specificity, and negative predictive values were similar to previously conducted research in patients with an increased risk for the development of breast cancer. 33 All other results are in line with previous studies conducted. [20][21][22]28,29,31 In recent years, MRI is sometimes used to find the cause of PND.…”
Section: Mando Dyko Filipe Et Alsupporting
confidence: 92%
“…No statistically significant changes were observed in the overall scores of the Breast-Q, SF-36 and EQ-5D-5L questionnaires at baseline compared to 2 weeks, 3 and 6 months after ductoscopy, indicating that ductoscopy does not negatively influence QOL. These findings further support the use of ductoscopy, which is performed more and more for both diagnostic and therapeutic purposes [26,34,35]. Additionally, this study showed that the all domains of Breast-Q, and EQ-5D-5L were stable over time and are thereby useful questionnaires for PND patients, while SF-36 was as a whole less useful and would require modifications.…”
Section: Discussionsupporting
confidence: 67%
“…Ductoscopy is often used to detect the cause underlying PND, which in the majority of cases is a benign lesion [23,35,[42][43][44][45]. A meta-analysis showed that ductoscopy has a sensitivity of 94% in detecting intraductal lesions of any type, but cannot reliably discriminate between benign and malignant lesions [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, ductoscopy is highly suitable for detecting benign lesions causing PND. 46,47,50,59,73,79 However, without histologic sampling of the lesions found, ductoscopy images alone cannot permit reliable discrimination between benign and malignant causes; endoscopic sampling during ductoscopy is not possible; and surgery may still be warranted to exclude malignancy. 24 Ductoscopy is not a cheap technique, like MRI is, so it may be especially useful when conventional imaging is negative.…”
Section: Discussionmentioning
confidence: 99%